The impact of new Canadian criminologist’s opinions on the criminal procedure - Shokoufe Pourhasan, Soraya Majidiani, Reza Fani, (Opción, 2019)
The purpose of this article is to provide a useful remedy for the implementation of justice for child offenders in all stages of the proceedings via qualitative comparative research methods. In result, today’s trend is to take remedial and curative measures for children and adolescents and many criminal justice laws have been formulated to protect the rights of children and re-socializing youth, which has been addressed by international agencies. In conclusion, the modern criminal law of different countries is in the direction of the evolution of the rules for young offenders and the attention of lawyers.